2019
DOI: 10.1002/mmce.21901
|View full text |Cite
|
Sign up to set email alerts
|

Direction of arrival estimation of mobile stochastic electromagnetic sources with variable radiation powers using hierarchical neural model

Abstract: Hierarchical neural model for an efficient one‐dimensional direction of arrival (DoA) estimation of stochastic electromagnetic (EM) sources with a variable radiation power is proposed. Model is trained to provide an azimuth position of such sources based on a spatial correlation matrix obtained by a signal sampling at a reception point and then used as an input to a neural model. It consists of two hierarchical levels realized by the multilayer perceptron (MLP)‐based neural networks. The first level is respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…As already shown in, 26,28 only cross-correlation elements in the first row of a normalized matrix C 0 without an autocorrelation element are sufficient to determine the positions of EM sources in the azimuthal plane. The real and imaginary parts of these elements are the inputs to the MLP network rather than their complex values, due to much easier training of the neural model.…”
Section: Ann-based Doa Modulementioning
confidence: 97%
See 3 more Smart Citations
“…As already shown in, 26,28 only cross-correlation elements in the first row of a normalized matrix C 0 without an autocorrelation element are sufficient to determine the positions of EM sources in the azimuthal plane. The real and imaginary parts of these elements are the inputs to the MLP network rather than their complex values, due to much easier training of the neural model.…”
Section: Ann-based Doa Modulementioning
confidence: 97%
“…On the other hand, in the version of the MLP DoA module developed in, 30 only the change in the distance between two antenna elements was considered and the change in the gains of the antenna elements was neglected. MLP networks were chosen to implement the DoA modules since they are suitable for modeling multidimensional nonlinear regression problems, such as DoA estimation, which was confirmed in our previous research 25,26 …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…These machine learning techniques have been applied to DOA estimation and source enumeration. The authors of [27][28][29] applied neural networks to DOA estimations, and the results showed that their neural networks based schemes can improve the performance of DOA estimations. Yang et al [30] proposed eigenvalue based deep neural networks for source enumeration, and the results showed that the proposed networks can achieve significantly better performance than the state-of-the-art methods in the low SNR regime.…”
Section: Related Workmentioning
confidence: 99%